2013
DOI: 10.1364/oe.21.018188
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy improvement of quantitative analysis by spatial confinement in laser-induced breakdown spectroscopy

Abstract: Hao, Z. Q.; Shen, M.; Xiong, W.; He, X. N.; Xie, Z. Q.; Gao, M.; Li, X. Y.; Zeng, X. Y.; and Lu, Yongfeng, "Accuracy improvement of quantitative analysis by spatial confinement in laser-induced breakdown spectroscopy" (2013

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 26 publications
0
32
1
1
Order By: Relevance
“…Guo et al 13 demonstrated that the size of the crater formed during ablative plasma formation can inuence detection sensitivity. Referenced pairs of emission lines for V (V I 440.85 nm and Fe I 438.35 nm), Cr (Cr I 425.43 nm and Fe I 425.08 nm) and Mn (Mn 476.64 nm and Fe 492.05 nm) were used to monitor elements present in trace amounts in a steel matrix.…”
Section: Ferrous Metalsmentioning
confidence: 99%
“…Guo et al 13 demonstrated that the size of the crater formed during ablative plasma formation can inuence detection sensitivity. Referenced pairs of emission lines for V (V I 440.85 nm and Fe I 438.35 nm), Cr (Cr I 425.43 nm and Fe I 425.08 nm) and Mn (Mn 476.64 nm and Fe 492.05 nm) were used to monitor elements present in trace amounts in a steel matrix.…”
Section: Ferrous Metalsmentioning
confidence: 99%
“…4 However, compared with other well-established atomic spectral analysis techniques, conventional LIBS performs not well in sensitivity and precision. In order to improve the analytical performance of LIBS, a large number of methods have been investigated, such as double-pulse, 5 spark discharge, 6 plasma confinement, 7 and so on. These methods mentioned above don't require sample preparation but need a more complex experimental setup.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies in which its accuracy and precision are addressed (Guo et al 2013;Axente et al 2014) and some techniques, for example, Double Pulse LIBS have actually contributed in improving these aspects (Harilal, Diwakar, and Hassanein 2013;Effenberger and Scott 2010;Khalil 2013).…”
Section: Introductionmentioning
confidence: 99%